A long way to Russia: Agustín de Betancourt - O. Volosyuk; Concepción Camarero Bullón (Ибероамериканские тетради, 2019)
A lot has been written about Agustín de Betancourt, his life in Russia, his contribution to the architecture, construction and organization of the transport system in the Russian Empire, as well as his life, his training and his professional career in Spain. However, little is known about when, how and why he makes the decision to leave his country permanently and settle in Russia. According to the documentation found in both Russian and Spanish archives, it has been shown that it is the Russian ambassador to Spain, Ivan Muravyov-Apostol, who, shortly after his arrival in Spain, at the end of 1803, after personally meeting Betancourt, proposes its contract to Saint Petersburg. Once the approval is obtained, the proposal is transferred. Also, the discrepancies between Manuel Godoy and Betancourt are studied in detail for the work of channeling the Genil river and the intervention in Soto de Roma, Royal Site owned by the minister, which marked the deterioration of the relations between both and took the engineer to consider, negotiate and accept the offer to settle in Russia. Both facts are studied within the framework of his professional career in Spain.